Kazakh traditional art of felt carpet (Journal of history, 2022)
The article reveals the history of the formation and features of the formation of the traditional Kazakh felt carpet (syrmak), nominational principles and ethno-cultural semantics of the types of felt carpet and their names. In addition to the practical application of the product, it was determined that the names of the felt carpet (syrmak) and the associated stable expressions and proverbs were one of the national values that served as a regulator of aesthetic, ethical, social use. The history of the origin and development of traditional Kazakh syrmaks is studied. Materials were collected on the types and components of felt carpet, their regional, generic characteristics, materials, place and purpose of use, customs and traditions, technological techniques. Depending on the types and methods of artistic expression, there are hundreds of names in our language, and some of them are still not contained in the explanatory, regional, sectoral, encyclopedic dictionaries of the modern Kazakh language. In addition to syrmak, other rafter items, bedding and horse equipment were also identified in the article. It was investigated that the Kazakh decorative and applied art is closely connected with the art and culture of other ethnic groups of the Turkic world, and the technology of the development of the art of quilting felt carpet was laid back in ancient historical times. The ethnocultural semantic analysis of the artistic and cognitive nature of the traditional Kazakh felt carpet of art in the Turkic culture is carried out.